The collective portrait of the Banū Birzāl - de Felipe, Helena (Anaquel de Estudios Árabes, 2025)
The aim of this paper is to reconstruct the collective portrait of the Banū Birzāl, a Berber nukkārite group that was exiled from the Maghrib to al-Andalus during the caliphate of al-Ḥakam II. The objective of this reconstruction is to highlight the effects that the changes in geographical, socio-political and religious contexts provoked in their collective biographical portrait, which, in certain periods, is transferred from the collectivity to certain individualities. The collective displacement of Banū Birzāl and the details of their historical trajectory allow us to draw some conclusions about their textual representationas a groupe, changes in both their leadership and their beliefs and, finally, about their mobility in the Mediterranean area.
Keywords: Prosopography; Ibadism; Banū Birzāl; Maghrib. al-Andalus